DOES INDUSTRIAL CLASSIFICATION OF FIRMS REFLECT CORPORATE PERFORMANCE? EVIDENCE FROM THE EUROPEAN UNION - Koralun-Bereznicka, Julia (European Scientific Journal, ESJ, 2015)
The aim of the study is to compare the industrial classification of firms in Europe (NACE) with the classification results based on corporate performance ratios. The methodology employed for this purpose includes mainly the k-means clustering technique as well as a similarity measure for evaluating the resemblance of grouping results. Using the total of almost 90 thousand aggregated observations from a sample of firms from 13 industries, 9 countries and 3 size groups, covering the period 2000-2010, findings provide evidence about the generally poor resemblance between the industrial classification and the grouping results based on financial ratios. There are also some country-wise differences found in the similarity level between the compared classifications.